Strategi Peningkatan Adopsi Masyarakat terhadap Urban Farming Toga di Hunian Padat Kota Solo - Arisnia Devie Hapsari; Retno Setyowati; Hanifah Ihsaniyati (Universitas Sebelas Maret, 2021)
This study aimed to identify internal and external factors and determine alternative strategies for improvement of communities’ adoption toga at crowded occupancy in Solo. Basic method of the research was descriptive qualitative. The technique of determining informants with the purposive sampling. The data was obtained through observation, deep interview, FGS, and document study. The research location was purposely determined by referring to active participation from communities in supporting the greening program in Solo, namely Serengan Urban Village. This urban village is quite active in supporting the greening program in Solo. The result showed that there were six strength and nine weaknesses as internal factors, seven opportunities and six threats as external factors. The result of IFE table showed that value of 3.058 meant strong and value in EFE of 2.915 meant medium. Based on the analysis of those two matrixes, it was found that the matrix result of IE was in category four, growing and building, so that in SWOT matrix, the researcher offered five strategies for improvement of urban farming TOGA adoption; (1) Improving experience and knowledge from communities to conduct urban farming TOGA, both in the cultivation and the utilization, 2) Improving communities’ awareness about the potential and opportunities of urban farming TOGA, 3) Improving communities’ ability to conduct the TOGA maintenance through assistance, 4) Improving communities’ knowledge and modal by building cooperation with other parties, 5) Encouraging farmers to build cooperation with government and other institutions for increasing experience in technology, maintenance, and sale.